Physical Activity Level, Depression, Anxiety, and Self-Perceived Health in Spanish Adults with Migraine: A Cross-Sectional Study - Iturra-Gonzalez, J (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Background: Of all neurological disorders, migraine is the second most prevalent in the world and the most disabling, affecting approximately 15% of the general population. It is characterized by recurrent headaches, along with other symptoms and comorbidities such as depression and anxiety, compromising the sufferer’s perception of health. Physical activity is a preventive treatment for migraine and its comorbidities. The aim is to analyze the relationship between migraine and physical activity levels (PAL) in the adult Spanish population, as well as PAL and depression, anxiety, and self-perceived health (SPH) in people with migraine. Methods: A cross-sectional study was conducted including 17,137 participants, 1972 with migraine, using data from the Spanish National Health Survey. Non-parametric statistical tests were performed: z-test for independent proportions (to analyze intergroup differences) and chi-square test (to analyze dependence between categorical variables). Results: Migraine was related to PAL (p < 0.001). Inactive people had a higher prevalence of migraine than active and very active people (p < 0.05). PAL was related to depression, anxiety, SPH, and analgesic use in people with migraine (p < 0.001). Inactive people had a higher prevalence of depression, anxiety, analgesic use, and negative SPH than active and very active people (p < 0.05). Conclusions: Increasing PA in the population could reduce the prevalence of migraine. In people with migraine, inactivity could worsen SPH and increase depressive and anxious symptoms. © 2022 by the authors.